The Effect of Magnesium, Boron, and NPK Fertilizer on the Growth of Pre-Nursery Oil Palm (Elaeis guineensis Jacq) - Sinaga, Daniel Perwiratama; Dwi Purbajanti, Endang; Adi Kristanto, Budi (Talenta Publisher, 2020)
Oil palm is one of Indonesia's main commodity plantation crops that can produce vegetable oil and this plant is consumptive of nutrients. This research aims to examine the effect of magnesium, boron, and NPK compound fertilizers and the interaction between magnesium, boron, and NPK compound fertilizers on the growth of oil palm seedlings. The research was conducted in February - May 2020 in a greenhouse with an altitude of 250 meters above sea level and the Laboratory of Ecology and Plant Production, Faculty of Animal and Agricultural Science, Diponegoro University. The research was conducted using a completely randomized design with a 4 Ã— 4 factorial with 3 replications. The first factor is the provision of no fertilizer, magnesium fertilizer, boron fertilizer, and magnesium + boron fertilizers. The second factor is the NPK compound at a dose of 1.8, 2.8, 3.8, and 4.8 g/seedling. The results showed that magnesium + boron had a significant effect on the stem diameter and root length and the NPK compound at a dose of 3.8 g/seedling could increase the stem diameter, fresh and dry weight of the root. The interaction between magnesium + boron fertilizer and NPK compound fertilizer had no significant effect on the height of the seedlings, the number of leaves, stem diameter, length of the root, and fresh and dry weight of the root. Keywords: Oil palm seedling, growth, nutrients, fertilizer dose